ALOKASI WAKTU DAN TINGKAT PARTISIPASI IBU RUMAH TANGGA PADA PERKEBUNAN CENGKEH - Alfira Yanamisra; Letty Fudjaja; Yopie Lumoindong (Hasanuddin University, 2019)
ALOKASI WAKTU DAN TINGKAT PARTISIPASIIBU RUMAH TANGGA PADA PERKEBUNAN CENGKEHdi Desa Garuntungan, Kabupaten Bulukumba, Provinsi Sulawesi Selatan Time Allocation and Level of Participation of Housewifes in the Clove Plantationat Garuntungan Village, Bulukumba District, South Sulawesi ProvinceAlfira Yanamisra*, Letty Fudjaja, Yopie LumoindongProgram Studi Agribisnis, Departemen Sosial Ekonomi PertanianFakultas Pertanian, Universitas Hasauddin, Makassar*Kontak penulis: alfirayanamisra2@gmail.comAbstractOne of commodities which have the role of agribusiness is clove commodity. It develops well in eastern Indonesia. The clove commodity developed by the farmers themselves together with their families which means it involves housewives in managing and regulating activities in the clove plantation business. This research aims to: 1) To determine the amount of time allocated for housewives in the clove plantation business; 2) To determine the level of participation of housewives in the clove plantation business; 3) To find out the factors that influence the level of participation of housewives in the clove plantation business and 4) To find out how much the income contribution of housewives of clove farmers to family income. This research was carried out in Garuntungan Village, Kindang District, Bulukumba District by using descriptive quantitative research methods. The study population was 402 households and selected 40 housewives who were determined using the Slovin formula. The results of the study concluded that: 1) The time allocation of housewives in the clove plantation business for productive activities in harvesting and post-harvest activities obtained results as much as ≥ 12 hours / day and outside harvesting activities ≥4 hours / day showed that housewives allocated time which is quite a lot for clove plantation business; 2) The level of participation of housewives in a high clove plantation business with 21 respondents with a percentage of 52.5%; 3) There are no relationship between participation factors and the level of participation of housewives seen from the four factors assessed: age, number of family dependents, level of education and length of effort, and 4) Contribution of housewives' income to the research location obtained a fairly low result of 12.56%. Keywords: time allocation, level of participation, housewife, clove plantation AbstrakSalah satu komoditi perkebunan yang memiliki peran agribisnis adalah cengkeh. Cengkeh dikeloka sendiri petani bersama keluarganya sehingga melibatkan ibu rumah tangga. Penelitian ini bertujuan untuk: 1) mengetahui besarnya alokasi waktu ibu rumah tangga pada usaha perkebunan cengkeh; 2) mengetahui tingkat partisipasi ibu rumah tangga pada usaha perkebunan cengkeh; 3) mengetahui faktor-faktor yang mempengaruhi tingkat partisipasi ibu rumah tangga pada usaha perkebunan cengkeh; dan 2) mengetahui kontribusi pendapatan ibu rumah tangga petani cengkeh terhadap total pendapatan keluarga. Penelitian dilaksanakan di Desa Garuntungan, Kecamatan Kindang, Kabupaten Bulukumba. Populasi penelitian sebanyak 402 rumah tangga dengan sampel 40 ibu rumah tangga. Hasil penelitian menyimpulkan bahwa: 1) Alokasi waktu ibu rumah tangga pada usaha perkebunan cengkeh untuk kegiatan produktif pada kegiatan panen dan pasca panen didapatkan hasil sebanyak ≥ 12 jam/hari dan di luar kegiatan panen ≥4 jam/hari menunjukkan bahwa ibu rumah tangga mengalokasikan waktu yang cukup banyak untuk usaha perkebunan cengkeh; 2) Tingkat partisipasi ibu rumah tangga pada usaha perkebunan cengkeh dengan kategori tinggi mencapai 52,5% dari populasi; 3) Tidak terdapat hubungan antara faktor-faktor partisipasi dengan tingkat partisipasi ibu rumah tangga dilihat dari umur, jumlah tanggungan keluarga, tingkat pendidikan dan lama berusahatani; dan 4) Kontribusi pendapatan ibu rumah tangga terhadap total pendapatan keluarga adalah 12,56%.Kata Kunci: alokasi waktu, tingkat partisipasi, ibu rumah tangga, usaha perkebunan cengkeh.